Peningkatan Kapasitas Kelompok Sadar Wisata dalam Mengembangkan Potensi Pariwisata dan Ekonomi Kreatif Kawasan Bandar Bakau Kota Dumai: Increasing the Capacity of Tourism Awareness Groups in Developing the Potential of Tourism and Creative Economy in the Bandar Bakau Area, Dumai City - Sidiq, Rd. Siti Sofro; Resdati, Resdati; Ihsan, Muhammad; Sulistyani, Andri; Sugiyanto, Seger (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
The purpose of the service is to increase the capacity of the tourism awareness group (Pokdarwis) in carrying out the duties and functions of developing Bandar Bakau ecotourism. To carry out this activity, the method that will be used is Participatory Rural Appraisal (PRA). The method involves more target communities actively by studying rural conditions and life and wants the community to share, improve, and analyze their knowledge of local conditions and life then make plans and then act or action. The partners or target community consisted of the Village Government, the Tourism Awareness Group (Pokdarwis), local communities and arts and culture activist groups. There are problems both from external and internal groups that have implications for less than optimal performance, namely lack of ability in institutional management and lack of ability to innovate and creatively develop existing potential. For this reason, the main activities of this service are Managerial, Technical, and Social Development as well as Innovation, Creativity, and Marketing Training. This activity went well where the response of the community and activity partners was very positive. Things that need to be followed up include providing intense mentoring and coaching efforts to Pokdarwis so that they become established and independent in carrying out their functions in developing Bandar Bakau Ecotourism